Intelligent data analysis for e-learning : enhancing security and trustworthiness in online learning systems /: enhancing security and trustworthiness in online learning systems. (2016) - Miguel, Jorge; Caballe, Santi, 1967-; Xhafa, Fatos
No abstract available